Parental conflict and adolescents’ socially adverse emotions: the mediating role of family functioning - Kong, Rong; Chen, Ruihua; Meng, Lingling (Frontiers in Psychology, 2024)
Objective: To examine the process of how parental conflict and family functioning influence adolescents' socially adverse emotions (shyness and loneliness). Methods: Stratified cluster sampling was used to conduct a questionnaire survey among 1,100 junior high school students from three junior high schools in Beijing, Chongqing and Shijiazhuang, China. Results: (1) The overall experience of adolescents' socially adverse emotions was at the moderate level; boys' experience of shyness and loneliness was significantly higher than that of girls; the experience of shyness and loneliness in the second grade was significantly higher than that in the first grade; (2) Parental conflict was significantly negatively correlated with family functioning and significantly positively correlated with adolescents' socially adverse emotions, while family functioning was significantly negatively correlated with adolescents' socially adverse emotions; (3) Family functioning partially mediates the relationship between parental conflict and adolescents' shyness and completely mediates the relationship between parental conflict and adolescents' loneliness. Conclusion: Compared to adolescents' shyness, family functioning plays a more important mediating role in the relationship between parental conflict and adolescents' loneliness.